Calculation of Number of Staff for Safe Evacuation in Elderly Medical Welfare Facilities - Seo Young, Kim; Ha Sung, Kong, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, the adequate number of staff that need to be allocated for evacuation of entire residents during daytime and night time through Pathfinder program. The adequate number of staff working for day and night shift were calculated in accordance with available evacuation time, fire brigade arrival time, and flashover occurrence time. As the result, when there are 48 residents, the adequate number of day shift staff for each evacuation time was 10 staff for 300 seconds, 5 staff for 430 seconds, and 4 staff for 540 seconds. As for the night time, considering there is fewer working staff, when there are 48 residents, the adequate number of night shift staff for each evacuation time was 13 staff for 430 seconds, 7 staff for 480 seconds, 6 staff for 540 seconds. In conclusion, 10 stationed day shift staff, and 6 stationed night shift staff is the adequate condition for safe evacuation. Henceforth, more researches regarding the evacuation time regarding the operation of firefighting facilities are needed.